The influence of environmental, social, and governance on financial performance with gender diversity as a moderating variable - Harfiahani Indah Rakhma Ningtyas (Indonesia Auditing Research Journal, 2025)
This study aims to analyze the moderating role of gender diversity in strengthening the relationship between ESG practices and financial performance in these companies in indonesia. Using panel data from 879 observations for the period 2019–2024. The results indicate that ESG has a positive and significant impact on ROA, while gender diversity also positively influences financial performance. Moreover, gender diversity significantly moderates the relationship between ESG and ROA, implying that higher female representation on boards strengthens the positive effect of ESG on corporate performance. These findings align with Stakeholder and Agency Theories, emphasizing importance of sustainable practices and inclusive governance in enhancing company profitability.